UPM captain hopes for a win - The Star, Ng Wei Loon (2009)
The Universiti Putra Malaysia (UPM) women's futsal team captain Syazwani Shahudin is urging her team mates, comprising employees of the university, to pull together in their bid to edge their counterparts from other public instutions of higher learning at a meet scheduled at the Universiti Malaysia Terengganu from June 3 to 13.